1993
DOI: 10.1677/jme.0.0110141
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the mouse thyrotrophin-releasing hormone receptor gene: an exon corresponds to a deletion in the rat cDNA

Abstract: The cloning and characterization of the mouse TRH receptor (TRH-R) gene revealed an untranslated exon (exon 1), a single intron and an upstream dinucleotide repeat sequence (d(TG)16.d(AG)21) in the 5' untranslated region (UTR). The coding region was contained almost entirely on a second exon (exon 2), with the final amino acid and stop codon at the COOH terminus of the gene encoded by a third exon (exon 3) flanked by two introns. The 3' UTR was contained on the remainder of exon 3 and on the final exon (exon 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…DISCUSSION We previously reported the existence of an intron in the coding region of the human TRHR gene based on its partial genomic sequence (17). The partial genomic sequence of the mouse TRHR has also recently been reported (13). However, the complete structure, including transcriptional start site, number of introns, and functional polyadenylation signals etc., has not been reported.…”
Section: Isolation and Characterization Of The Human Trhr Gene-mentioning
confidence: 89%
See 2 more Smart Citations
“…DISCUSSION We previously reported the existence of an intron in the coding region of the human TRHR gene based on its partial genomic sequence (17). The partial genomic sequence of the mouse TRHR has also recently been reported (13). However, the complete structure, including transcriptional start site, number of introns, and functional polyadenylation signals etc., has not been reported.…”
Section: Isolation and Characterization Of The Human Trhr Gene-mentioning
confidence: 89%
“…There are several d(TG) n dinucleotide repeats present in the 5Ј-region of the human TRHR gene, similar to the mouse TRHR gene (13). These repeats are often found in areas that serve as regulatory elements for gene expression and are thought to be potential Z-DNA-forming sequences.…”
Section: Isolation and Characterization Of The Human Trhr Gene-mentioning
confidence: 99%
See 1 more Smart Citation
“…These are TRH receptor 1 (TRH-R1), which is the primary (or only) receptor in TSH-secreting cells, and TRH-R2, which is expressed throughout the CNS along with TRH-R1 but typically in different areas of the brain (O’Dowd et al, 2000; Sun et al, 2003). In humans, by contrast, only a single type of receptor for TRH, TRH-R, is expressed that is more similar to TRH-R1 than TRH-R2 (Duthie et al, 1993; Matre et al, 1993). It has been reported that TAL binds with lower affinity than TRH to receptors in rat or mouse pituitary and in brain tissue preparations (Kinoshita et al, 1997; Asai et al, 1999, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The mapped intron 2 seemed at first to be a unique feature of the human TRHR as no intron was found in the ORF of the mouse and rat TRHR genes (de la Pena et al, 1992 b ; Duthie et al, 1993 ; Satoh et al, 1993 b ). To extend the evolutionary perspective of our finding, we set out to determine whether the large intron 2 of the TRHR gene was present in chimpanzee and sheep genomic DNA.…”
Section: Detection Of Intron 2 Of Trhr In Chimpanzee and Sheep Genomimentioning
confidence: 99%